(untitled) (Communications in Mathematical Research, 2024)
Let L=−∆+V be a Schrödinger operator, where ∆ is the Laplacian on R^d and the nonnegative potential V belongs to the reverse Hölder class B_d/2. In this paper, we define a new version of Carleson measure associated with the fractional heat semigroup of Schrödinger operator L. We will characterize the Campanato spaces and the predual spaces of the Hardy spaces by the new Carleson measure.